UJI POTENSI EKSTRAK ETANOL BAWANG LANANG HITAM (Allium sativum L.) DALAM PENURUNAN KADAR KADMIUM DENGAN SPEKTROFOTOMETRI SERAPAN ATOM (SSA) - Ayu Trisnawati, Febiana; Ingrid Anggraini, Devina; Wisnu Kusuma, Eka (Sekolah Tinggi Ilmu Kesehatan Nasional & Pengurus Cabang Ikatan Apoteker Indonesia (IAI) Sukoharjo, 2024)
Pollution caused by the discharge of waste into the waters will have an impact on water quality. Pollutants that can reduce water quality are heavy metal cadmium. Cadmium heavy metal when it enters the human body can cause toxic effects. The body needs an antidote to lower metal levels. Black onion (Allium sativum L.) contains flavonoids which are used as chelating agents. This study aims to determine the best concentration of ethanolic extract of black onion (Allium sativum L.) which can reduce cadmium levels maximally. The ethanolic extract of black onion was made in five concentration series, namely 0.2 ppm, 0.4 ppm, 0.6 ppm, 0.8 ppm, and 1 ppm. Cadmium metal (Cd) 20 ppm was treated with the addition of each concentration of black onion ethanol extract. The solution was separated with chloroform. The aqueous phase is an excess of cadmium metal which was analyzed by Atomic Absorption Spectrophotometry (AAS) at a wavelength of 228.8 nm. The results obtained showed that the best concentration of 0.8 ppm black onion ethanol extract could reduce metal cadmium (Cd) maximally which showed a percentage of 66.3906% with a coefficient of variation of 1.5873%.